Ecology and Behavior of Assamese Monkeys in Shivapuri Nagarjun National Park, Nepal - Chalise, Mukesh K; Bhattarai, Gopal Prakash; Pandey, Bishnu (Journal of Natural History Museum, 2015)
The population distribution and diurnal behavior of Assamese monkey Macaca assamensis were studied in Shivapuri Nagarjun National Park, Nepal and data collected during Dec. 2011 to March 12 by scan sampling methods along with application of ArcGIS software. Seven bisexual troops were observed in subtropical/lower temperate forest of Shivapuri Nagarjun National Park and its marginal areas near to human settlement. The observed smallest troop was with 12 individuals while the largest troop had 35 individuals of different age. The average troop size is 23.71 with standard deviation 9.22. Out of three broad age groups adults were 40.27%, immature 42.95% and infants were 14.09 %. The sex ratio between male and female was 1:1.03. A troop was selected as focal troop for behavioral study after habituation. Foraging/eating covered 46% of total observed time while resting 19%, locomotion 16%, sleeping 12%, grooming 6%, and playing 1%. Some other behavior noticed such as aggression, copulation, stone licking, coughing and sniffing for short duration. Young and tender leaves as well as burgeoning twigs were primary sources of food (38.24 %) for winter followed by seeds (35.29%, moss and epiphytes (14.71%), insects (5.88%) and others 5.88%. while water drinking was never observed. All troops in Shivapuri forest were found residing on the steep cliffs along with river bank while Nagarjun forest troops used cliff as well as tall trees. J. Nat. Hist. Mus. Vol. 27, 2013: 12-24